A common thermal niche among geographically diverse populations of the widely distributed tree species Eucalyptus tereticornis : No evidence for adaptation to climate‐of‐origin - John E. Drake; Angelica Vårhammar; Dushan Kumarathunge; Belinda E. Medlyn; Sebastian Pfautsch; Peter B. Reich; David T. Tissue; Oula Ghannoum; Mark G. Tjoelker (Global Change Biology, 2017)
Impacts of climate warming depend on the degree to which plants are constrained by adaptation to their climate‐of‐origin or exhibit broad climatic suitability. We grew cool‐origin, central and warm‐origin provenances of Eucalyptus tereticornis in an array of common temperature environments from 18 to 35.5°C to determine if this widely distributed tree species consists of geographically contrasting provenances with differentiated and narrow thermal niches, or if provenances share a common thermal niche. The temperature responses of photosynthesis, respiration, and growth were equivalent across the three provenances, reflecting a common thermal niche despite a 2,200 km geographic distance and 13°C difference in mean annual temperature at seed origin. The temperature dependence of growth was primarily mediated by changes in leaf area per unit plant mass, photosynthesis, and whole‐plant respiration. Thermal acclimation of leaf, stem, and root respiration moderated the increase in respiration with temperature, but acclimation was constrained at high temperatures. We conclude that this species consists of provenances that are not differentiated in their thermal responses, thus rejecting our hypothesis of adaptation to climate‐of‐origin and suggesting a shared thermal niche. In addition, growth declines with warming above the temperature optima were driven by reductions in whole‐plant leaf area and increased respiratory carbon losses. The impacts of climate warming will nonetheless vary across the geographic range of this and other such species, depending primarily on each provenance's climate position on the temperature response curves for photosynthesis, respiration, and growth.